The white book - Han, Kang, 1970-; Smith, Deborah, 1987- (2019)
A lyrical exploration of personal grief, conveyed through the prism of the color white, finds a nameless writer grappling with a haunting family tragedy involving the infancy death of her older sister.
"This translation originally published in Great Britain by Portobello Books, London in 2017. This edition published by arrangement with Portobello Books."--Title page verso.
Keywords: Suffering -- Fiction; Resilience (Personality trait) -- Fiction; Grief -- Fiction; Sisters -- Death -- Fiction; Authors -- Fiction; FICTION -- Psychological; FICTION -- Literary; FICTION -- Cultural Heritage; Suffering -- Fiction; Resilience (Personality trait) -- Fiction; Children -- Death -- Fiction; White -- Fiction